Zoster and its lurking shadow - Hina Handa; Balaji Gandhi Babu Dara; Giridhar S Naidu; Ashwini Deshpande (Wolters Kluwer Medknow Publications, 2016)
A large number of oral mucosal lesions result in severe post-affliction deficits. One such defect is neurological fall out. Herpes zoster is a condition that occasionally results in a dreadful post-infection neuralgic pain. Although shingles is generally regarded as a self-limited condition, it can take several weeks to resolve and has the potential for development of complications. To identify this as well as appropriate management is required. Patients affected are in such severe distress that alleviation of pain and successful treatment protocol should be the primary consideration. We report one such case, which was successfully treated, and also intend to highlight the current concepts in the management of such cases.